2014
DOI: 10.1186/1475-2875-13-439
|View full text |Cite
|
Sign up to set email alerts
|

Open-label, randomized, non-inferiority clinical trial of artesunate-amodiaquine versus artemether-lumefantrine fixed-dose combinations in children and adults with uncomplicated falciparum malaria in Côte d'Ivoire

Abstract: BackgroundEmergence of artemisinin resistance has raised concerns that the most potent anti-malarial drug may be under threat. Artesunate-amodiaquine (AS-AQ) and artemether-lumefantrine (AL) are, respectively, the first- and second-line treatments for uncomplicated falciparum malaria in Côte d’Ivoire. Constant monitoring by National Malaria Control Programme (NMCP) of drug efficacy is an important tool in establishing rational anti-malarial drug policies in Côte d’Ivoire.MethodsIn an open label, randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…Results from these studies demonstrated an estimated PCT of 48 hours for both AS + AQ and AL. 18 , 19 , 26 However, these estimations of PCT have some limitations. Determination of PCT based on daily sampling lacks precision since the exact time of parasite count is not recorded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from these studies demonstrated an estimated PCT of 48 hours for both AS + AQ and AL. 18 , 19 , 26 However, these estimations of PCT have some limitations. Determination of PCT based on daily sampling lacks precision since the exact time of parasite count is not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…P. falciparum is the predominant malaria parasite, accounting for more than 95% of malaria infections. 18 Bouake region was the epicenter of the country’s military crisis in 2002. During this period, the NMCP’s guidelines for malaria treatment were not followed by physicians.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2006, two ACT formulations, artemether–lumefantrine (AL) and artesunate–amodiaquine (ASAQ), were chosen by the National Malaria Control Programme to treat uncomplicated malaria in Mali. Many studies showed that AL and ASAQ remained efficacious against uncomplicated falciparum malaria in Africa [ 1 3 ] and data on clinical efficacy, safety and tolerability of AL and ASAQ exists in Mali [ 4 , 5 ]. Dihydroartemisinin–piperaquine (DHA–PQ) is also recommended by the WHO for uncomplicated malaria in Africa but, few data are available on its clinical efficacy and safety [ 6 , 7 ] but little is know on DHA–PQ combination.…”
Section: Introductionmentioning
confidence: 99%
“…These two ACTs have been shown to be highly effective against acute uncomplicated falciparum malaria in these two countries. 2,3 Elsewhere in sub-Saharan Africa, high cure rates, often attaining > 95% after polymerase chain reaction (PCR) correction to exclude reinfections, have been reported with nearly all ACTs. 4 Artemisinin-resistant Plasmodium falciparum was first reported from Cambodia in 2008.…”
mentioning
confidence: 99%